A comparison of the efficacy of the effect of online versus face-to-face group counseling based on positive-approach on sexual intimacy of women after benign abdominal hysterectomy: a clinical trial - Orly Nazanin Kalimi; Tayebeh Mokhtari Sorkhani; Ali Dehghani; Mahshid Bokaie (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective The study investigates the influence of positive-approach counseling through both online and face-to-face group therapy on the sexual intimacy of women after benign complete abdominal hysterectomy, addressing challenges such as the loss of femininity and other psychosexual complications that disrupt the couple’s relationship post-surgery. Methods This is a parallel clinical trial, conducted in 2023 in Yazd, Iran; with sixty-six participants post- benign complete abdominal hysterectomy were randomly assigned to online and face-to-face counseling groups. Each group had eight 90-minute sessions, and data were collected using demographic and intimacy scale (IS) questionnaires at baseline, eighth week, and twelfth week follow-up. Statistical analysis used SPSS version 23 (P < 0.05). Results In the Online Group, the mean sexual intimacy score significantly increased from 72.42 ± 9.05 to 87.06 ± 7.98 at eight weeks and 90.30 ± 8.23 at twelve weeks (P < 0.001). In the Face-to-Face Group, the mean score increased from 70.21 ± 6.75 to 81.24 ± 5.55 at eight weeks and 85.03 ± 5.40 at twelve weeks (P < 0.001). Online counseling proved more effective than face-to-face counseling in enhancing sexual intimacy (P = 0.043). Conclusion Online and face-to-face counseling based on the positive approach improved sexual intimacy in women with a history of benign hysterectomy. Moreover, it seems that online counseling was more effective, so it is recommended that this method be employed in follow-up sessions after hysterectomy. Iranian Registry of Clinical Trials - IRCT20230209057373N1